Establishment of an infectious clone of the porcine transmissible gastroenteritis virus and a study on the location and function of accessory protein 3 - Zhenye Hao; Zhenye Hao; Lifei Liu; Lifei Liu; Shuai Wang; Shuai Wang; Yanping Jiang; Yanping Jiang; Jiaxuan Li; Jiaxuan Li; Wen Cui; Wen Cui; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionTransmissible gastroenteritis virus (TGEV), as the causative agent of TGE, causes huge economic losses in the pig industry worldwide.MethodsIn this study, we successfully constructed a reverse genetic system for the TGEV TH-98 strain and rescued the recombinant virus rTH-98-Δ3-COE-HA based on this system.ResultsThe results showed that ORF3 is a non-structural protein and does not exist in mature virions. Therefore, rTH-98-Δ3-COE-HA induced inflammatory cytokine expression in IPEC-J2 cells, but the expression levels were significantly lower than those triggered by TH-98 and rTH-98, indicating that TGEV ORF3 may play a critical role in inducing the host immune response. To detect whether the exogenous protein expressed in the rTH-98-Δ3-COE-HA has immunogenicity, the results showed that the levels of antibodies were significantly increased in mice. rTH-98-Δ3-COE-HA can induce a specific immune response in the host body against its expressed exogenous proteins.Discussion and conclusionOur study provides important clues for revealing the role of ORF3 in virus replication and pathogenesis, laying a theoretical and material foundation for the construction of recombinant viral multi-valent vaccines.